SOMASCAN AS A DISCOVERY PLATFORM TO IDENTIFY PLASMA PROTEIN BIOMARKERS FOR POSTOPERATIVE DELIRIUM - Libermann, T A (Innov Aging, 2018)
Currently, no blood-based biomarkers exist to predict incidence of postoperative delirium. We used SOMAscan, an aptamer-based proteomics platform, to identify plasma proteins associated with delirium. SOMAscan protein profiles were generated from samples obtained preoperatively (PREOP) and on postoperative day 2 (POD2) from 18 delirium cases and matched controls from SAGES, a cohort of elderly patients undergoing elective surgery. A 7-protein PREOP and a 4-protein POD2 Support Vector Machine-based model distinguish between delirium and no delirium (AUC 0.94 for both). Independent ELISA validation from 63 SAGES matched pairs confirmed that higher levels of one protein common to PREOP and POD2 models, YKL-40, a neuroinflammatory marker, was a risk marker for delirium at PREOP (p-value<10–4; AUC 0.73) and a disease marker on POD2 (p-value<0.003; AUC 0.83). This study demonstrates the feasibility of SOMAscan proteomics to identify potential delirium plasma biomarkers and advances our understanding of the importance of neuroinflammation in delirium pathophysiology.